2009
DOI: 10.1186/1475-2891-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Plasma micronutrient status is improved after a 3-month dietary intervention with 5 daily portions of fruits and vegetables: implications for optimal antioxidant levels

Abstract: To explore the effects of increasing fruit and vegetable intake and the resulting effects on levels of circulating micronutrients in a community-dwelling population with an already high consumption of fruits and vegetables, 112 volunteers (86% women) underwent targeted dietary counseling for three months. At the beginning of the study and after 4, 8 and 12 weeks a food frequency questionnaire was filled in, and plasma levels of dietary antioxidants as well as biomarkers of oxidative lipid and protein damage we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 8 publications
6
25
0
Order By: Relevance
“…More recently, a study on the supplementation with purified lycopene [224] confirmed that at high dose of 30 mg lycopene/day decreased DNA oxidative damage in lymphocytes and urinary 8-hydroxy-deoxyguanosine while no significant differences were observed for glucose, lipid profile and other biomarkers of lipid peroxidation. Conversely, the study of Polidori et al [230] showed that a good nutritional program (3 month dietary intervention), while improving plasma levels of antioxidants, did not provoke a decrease of oxidative stress biomarkers.…”
Section: Interventional Studiesmentioning
confidence: 93%
“…More recently, a study on the supplementation with purified lycopene [224] confirmed that at high dose of 30 mg lycopene/day decreased DNA oxidative damage in lymphocytes and urinary 8-hydroxy-deoxyguanosine while no significant differences were observed for glucose, lipid profile and other biomarkers of lipid peroxidation. Conversely, the study of Polidori et al [230] showed that a good nutritional program (3 month dietary intervention), while improving plasma levels of antioxidants, did not provoke a decrease of oxidative stress biomarkers.…”
Section: Interventional Studiesmentioning
confidence: 93%
“…The authors concluded that the surprising behavior of the MDA may be the result of insufficient ingestion of antioxidants from the diet and could be associated to the insignificant (p>0.05) increase in the levels of α-tocopherol. 92 This same biomarker (MDA) was analyzed in a study conducted in Spain. The authors identified that the ingestion of cooked vegetables above 154.9 grams and moderate ingestion of wine (150 mL) are protectors against oxidative damage (plasmatic MDA).…”
Section: Nutritional Status and Oxidative Stressmentioning
confidence: 99%
“…The plasma was stored at –80°C until analysis for carotenoids such as lycopene, α-, and β-carotene by high-performance liquid chromatography, as previously described [6, 17, 18]. In addition, the colorless carotenoids phytofluene and phytoene were measured because these precursors of carotenoids absorb radiation in the UV range [19, 20].…”
Section: Methodsmentioning
confidence: 99%